A pharmacoeconomic study of traditional anticoagulation versus direct oral anticoagulation for the treatment of venous thromboembolism in the emergency department. Issue 5 (11th February 2016) - Law, Stephanie; Ghag, Daljit; Grafstein, Eric; Stenstrom, Robert; Harris, Devin
Abstract: Objectives: Patients with venous thromboembolism (VTE) (deep vein thrombosis [DVT] and pulmonary embolism [PE]) are commonly treated as outpatients. Traditionally, patients are anticoagulated with low-molecular-weight heparin (LMWH) and warfarin, resulting in return visits to the ED. The direct oral anticoagulant (DOAC) medications do not require therapeutic monitoring or repeat visits; however, they are more expensive. This study compared health costs, from the hospital and patient perspectives, between traditional versus DOAC therapy. Methods: A chart review of VTE cases at two tertiary, urban hospitals from January 1, 2010 to December 31, 2012 was performed to capture historical practice in VTE management, using LMWH/warfarin. This historical data were compared against data derived from clinical trials, where a DOAC was used. Cost minimization analyses comparing the two modes of anticoagulation were completed from hospital and patient perspectives. Results: Of the 207 cases in the cohort, only 130 (63.2%) were therapeutically anticoagulated (international normalized ratio 2.0–3.0) at emergency department (ED) discharge; patients returned for a mean of 7.18 (range: 1–21) visits. Twenty-one (10%) were admitted to the hospital; 4 (1.9%) were related to VTE or anticoagulation complications. From a hospital perspective, a DOAC (in this case, rivaroxaban) had a total cost avoidance of 1, 488.04 per VTE event, per patient. From a patient perspective, it would cost an additional 204.10 to 349.04 over 6 months, assuming no reimbursement. Conclusions: VTE management in the ED has opportunities for improvement. A DOAC is a viable and cost-effective strategy for VTE treatment from a hospital perspective and, depending on patient characteristics and values, may also be an appropriate and cost-effective option from a patient perspective. RÉSUMÉ: Objectif: Les patients souffrant d'une thromboembolie veineuse (TEV) (thrombose veineuse profonde [TVP] ou embolie pulmonaire [EP]) sont souvent traités en consultation externe. L'anticoagulation se réalise habituellement par l'héparine de faible masse moléculaire (HFMM) et par la warfarine, ce qui nécessite des consultations ultérieures au service des urgences (SU). Il existe aussi l'anticoagulation orale directe (AOD), qui ne nécessite pas de surveillance thérapeutique ou de consultations rapprochées, mais son coût est plus élevé que celui du traitement classique. L'étude décrite ici visait donc à comparer les coûts, liés aux soins de santé, de l'anticoagulation classique avec ceux de l'AOD, et ce, tant pour les hôpitaux que pour les patients. Méthode: Les auteurs ont procédé à un examen des dossiers des cas de TEV traités dans deux hôpitaux urbains, de soins tertiaires, pour la période du 1 er janvier 2010 au 31 décembre 2012, afin de recueillir des données sur la pratique historique du traitement de la TEV par l'HFMM et la warfarine. Il y a eu par la suite comparaison des données historiques avec celles provenant d'essais cliniques d'anticoagulants oraux directs. Enfin, des analyses de minimisation des coûts ont été effectuées afin que soient comparés les coûts des deux modalités de traitement anticoagulant, et ce, tant pour les hôpitaux que pour les patients. Résultats: La cohorte comptait 207 cas et, dans seulement 130 (63, 2 %) d'entre eux, le degré d'anticoagulation était suffisant sur le plan thérapeutique (RIN : 2, 0 – 3, 0) au moment du congé du SU; le suivi des patients a nécessité en moyenne 7, 18 (plage : 1-21) consultations. Vingt et un (10 %) patients ont été hospitalisés, dont 4 (1, 9 %) pour des complications liées à la TEV ou à l'anticoagulation. Du point de vue des hôpitaux, l'AOD (en l'occurrence, le rivaroxaban) a permis d'éviter des coûts totaux de 1488, 04 par TEV, par patient. Du point de vue des patients, le traitement entraînerait des coûts additionnels variant de 204, 10 à 349, 04 sur une période de six mois, en cas de non-remboursement. Conclusions: Il y a place à l'amélioration dans la prise en charge de la TEV au SU. L'AOD se montre une stratégie durable et rentable du traitement de la TEV pour les hôpitaux; elle peut aussi se révéler une modalité appropriée et rentable pour les patients, selon les caractéristiques et les valeurs de chacun.